TB drug susceptibility testing in high fluoroquinolone resistance settings - F. Saluzzo; F. Masood; V. Batignani; F. Di Marco; U. Majeed; A. Ghazal; D.M. Cirillo; S. Tahseen (IJTLD Open)
BACKGROUND: The insurgence of resistance to key drugs of the BPaLM (bedaquiline + pretomanid + moxifloxacin) regimen is a major concern. In settings with widespread resistance to fluoroquinolones (FQs), like Pakistan, new technologies, such as Xpert® MTB/XDR, may ensure drug resistance upfront screening. This study aims to assess MTB/XDR's performance in detecting FQs and isoniazid resistance, proposing a renewed diagnostic algorithm for drug-resistant TB (DR-TB). METHODS: This cross-sectional prospective study, approved by the local ethical committee, collected samples from people newly and previously diagnosed with TB over 6 months. Xpert® MTB/RIF Ultra, MTB/XDR, Genotype® MTBDRplus, Genotype® MTBDRsl, culture, and phenotypic drug susceptibility testing (pDST) for relevant drugs (including bedaquiline and levofloxacin) were performed. Next-generation sequencing (NGS) resolved discordances between MTB/XDR and pDST results. RESULTS: The analysis showed that MTB/XDR has 91.5% and 88.2% sensitivity and 99.5% and 97.7% specificity in detecting respectively isoniazid (INH) and resistance to FQs, demonstrating that MTB/XDR meets the WHO targets for INH resistance detection at the peripheral level. NGS effectively resolved discordances between MTB/XDR and pDST results. CONCLUSIONS: The obtained results allowed designing the proposed diagnostic algorithm for rapid identification of DR-TB, ensuring rapid and equitable access to drug susceptibility testing for TB, ultimately improving TB care and control.